Measurements of Mixing Enthalpy for a Lead-Free Solder Bi-In-Sn System - Kumar M.R.; Mohan S.; Behera C.K. (My University, 2025)
Measurements of mixing enthalpy for a Bi-In-Sn system needs special attention as far as the lead-free solder applications are concerned. Lead-free solder is generally used for solder joints in electronic equipment. In this work, an MHTC 96 Line Evo (Setaram Instruments, France) drop-solution calorimeter was used to determine the integral enthalpy of mixing for a Bi-In-Sn system at 767 K, 813 K and 855 K using drop technique. The enthalpy of mixing was measured for three different cross sections of (Sn0.33Bi0.67)1−x Inx, (Sn0.50Bi0.50)1−x Inx and (Sn0.67Bi0.33)1−x Inx. Indium was dropped onto the Bi-Sn alloys over the entire composition of indium. Partial quantities of indium mixing were calculated from the integration of the heat flow curve using CALISTO software. Subsequently, integral molar quantities of mixing were calculated from the partial quantities. Mixing enthalpy was found to be almost temperature-independent in the Bi-In-Sn system. Iso-enthalpy curves for the integral mixing enthalpy were plotted at 813 K. The data from this study were analysed with a least-squares fit using the Redlich–Kister–Muggianu polynomial to determine the ternary interaction parameter. © 2019, The Minerals, Metals & Materials Society.